Application of Stranded Pelagic Sargassum Biomass as Compost for Seedling Production in the Context of Mangrove Restoration - Trench, Camilo; Thomas, Shanna-Lee; Thorney, Delroy; Maddix, Gina-Marie; Francis, Patrice; Small, Hugh; Machado, Carla Botelho; Webber, Dale; Tonon, Thierry; Webber, Mona (Frontiers in Environmental Science, 2022)
The Sargassum spp. inundations across the Atlantic and Caribbean that began in 2011 have continued unabated and new uses for the biomass are being continuously explored. Mangroves protect shorelines, store carbon, enhance water quality and promote biodiversity. Their restoration can be hindered by poor soils associated with urbanized coastlines. Sargassum spp. application in the form of mulch, compost and plant tonics has yielded positive results in a range of plants. As part of transforming the inundations to benefit communities, Sargassum spp. compost (SC) was assessed in mangrove seedling production for restoration. Pure SC was mixed with soil/sand medium, as different treatments, for the production of Rhizophora mangle seedlings in ‘wet’ and ‘dry’ nurseries. Plants in the ‘wet’ nursery performed poorly, with 90-100% of plants in 50 and 100% SC, respectively, dying after six weeks. Seedlings in all SC treatments in the ‘dry’ nursery survived with obvious and statistically significant treatment differences. Height and number of leaves indicated best growth in the 75% SC treatment while the control (0% SC) had poorest growth. Seedling health, greatest in the control, was poorest in 50 and 100% SC. Elemental analysis of SC, seedlings and soil/sand medium indicated that several elements (Na, K, Ca, As, Se) found in high concentrations in the SC, were low in the plants. Overall, low sequestration of elements by mangrove seedlings, and the reported ability of mangrove soils to reduce element mobilization through chelation, indicate potential for use of Sargassum spp. in soil amelioration for mangrove restoration without proportional contamination of the ecosystem. We see potential for the use of nuisance Sargassum spp. blooms to support mangrove restoration, leading to increased benefits to coastal communities who are being affected by the inundations.